Escaping the Holocaust: Human and health capital of refugees to the United States, 1940-42 - Matthias Blum; Claudia Rei (Queen's University Centre for Economic History (QUCEH), 2015)
The large-scale persecution of Jews during World War II generated massive refugee movements. Using data from 20,441 predominantly Jewish passengers from 19 countries traveling from Lisbon to New York between 1940 and 1942, we analyze the last wave of refugees escaping the Holocaust and verify the validity of height as a proxy for human and health capital. We further show this episode of European migration displays well-known features of migrant self-selection: early migrants were taller than late migrants; a large migrant stock reduces migrant selectivity; and economic barriers to migration apply. Our findings show that Europe experienced substantial losses in human and health capital while the US benefitted from the immigration of European refugees.
Keywords: N32; N34; N42; N44; F22; J24; O15; 330; migration; refugees; World War II; Holocaust; Germany; New York